Comparison of Zidovudine and Tenofovir Based Regimens With Regard to Health-Related Quality of Life and Prevalence of Symptoms in HIV Patients in a Kenyan Referral Hospital - Jilian O. Etenyi; Jilian O. Etenyi; Faith A. Okalebo; Faith A. Okalebo; Margaret Oluka; Margaret Oluka; Kipruto A. Sinei; Kipruto A. Sinei; George O. Osanjo; George O. Osanjo; Amanj Kurdi; Amanj Kurdi; et al. (Frontiers Media S.A., 2018)
Aim: Zidovudine and tenofovir form the backbone of antiretroviral therapy in Kenya. However, their side-effects may affect the quality of life (QoL) of patients. The aim was to compare the health-related quality of life (HRQoL) of adult patients on tenofovir versus zidovudine based regimens in a referral hospital in Kenya to provide future guidance.Methods: A comparative cross sectional study among 501 adult out-patients on either tenofovir or zidovudine was undertaken in Kenyatta National Hospital between 2015 and 2016. The Medical Outcome Study HIV Health Survey (MOS-HIV) was administered along with other key aspects of treatment. Linear regression analysis was performed to identify determinants of HRQoL.Results: Patients on zidovudine had a higher Physical Health Summary Score (PHSS) and Mental Health Summary Score (MHSS) compared to those on tenofovir. The presence of any symptom of the disease and a stated inability to cope were negatively associated with PHSS, whilst having a regular source of income improved PHSS. Being on tenofovir, symptom of illness [β = -1.24; 95% CI (-2.253, -0.226)], absence of pain [β=0.413; 95% CI (0.152, 0.674)] and patient stated inability to cope with HIV [β = -1.029; 95% CI (-1.441, -0.617)] affected the MHSS. Patients on tenofovir and second line regimens had more signs and symptoms of illness.Conclusion: Participants on zidovudine based regimens showed a better performance across all aspects of HRQoL. These are considerations for the future.